Using the SIR Model as a Guideline for Vaccination during an Infectious Disease - Vivek Ily (International Journal of Mathematics And its Applications, 2020)
In this paper, we discuss and analyze the well-known Susceptible-Infected-Recovered (SIR) Model to address the following questions: (Q1) What total proportion of the population will get infected? (Q2) What proportion of the population should be vaccinated in order to suppress the epidemic? To answer these questions, we discuss and analyze and the SIR model and its variations to predict the outcome of an epidemic and any measures needed to suppress the outbreak of the disease.